2006
DOI: 10.1017/s1138741600006065
|View full text |Cite
|
Sign up to set email alerts
|

Is Sexual Attraction Independent of the Instrumental and Expressive Traits?

Abstract: Sexual attraction is an essential part of sex, just as the instrumental and expressive traits are the mainstay of gender. Various hypotheses concerning the dimensionality and independence versus dependence/overlapping of these core entities were tested. A group of 423 university students completed the Sexual Attraction Questionnaire (SAQ; Fernández, Quiroga, & Rodríguez, 2006) and the 12-item Bem Sex Role Inventory (BSRI; Bem, 1974). Internal consistency and factor analyses (PAF) were conducted. The results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…This may be why scientific studies on love have increased since the 1960s, and especially as of the 1980s (Alberoni, 1990;Barrón, Martínez-Íñigo, De Paúl, & Yela, 1999;Bauman, 2005;Bloom, 1967;Carreño, 1991;Fisher, 1992;Lampert, 1997;Sangrador, 1993;Sternberg, 1988Sternberg, , 1998Sternberg & Barnes, 1988;Sternberg & Grajek, 1984;Sternberg & Weis, 2006;Yela, 2000Yela, , 2006. Something similar occurred with the studies on the psychology of sexual behavior (Fernández, Quiroga, & Del Olmo, 2006;Wiseman, 1976), a behavior that is a fundamental component of love (Critelli, Myers, & Loos, 1986).…”
supporting
confidence: 57%
“…This may be why scientific studies on love have increased since the 1960s, and especially as of the 1980s (Alberoni, 1990;Barrón, Martínez-Íñigo, De Paúl, & Yela, 1999;Bauman, 2005;Bloom, 1967;Carreño, 1991;Fisher, 1992;Lampert, 1997;Sangrador, 1993;Sternberg, 1988Sternberg, , 1998Sternberg & Barnes, 1988;Sternberg & Grajek, 1984;Sternberg & Weis, 2006;Yela, 2000Yela, , 2006. Something similar occurred with the studies on the psychology of sexual behavior (Fernández, Quiroga, & Del Olmo, 2006;Wiseman, 1976), a behavior that is a fundamental component of love (Critelli, Myers, & Loos, 1986).…”
supporting
confidence: 57%
“…The internal consistency values obtained till now are high for both scales: Attraction to Men and Attraction to Women (α = .98 and α = .97, respectively, in diverse studies and for different versions of the SAQ, 22 items and 17 items). The cluster and factor analyses carried out with the different versions of the SAQ have corroborated the hypothesis of one bipolar factor or-conceptually, the same-two inversely related factors, according to various studies (Fernández et al, 2006b;Fernández, Quiroga, & Rodríguez, 2006).…”
Section: Temporal Stability and Cross-national Of The Saqmentioning
confidence: 56%
“…The starting point of this approach is apparent sexual dimorphism, whose explanatory mechanisms are relatively well-known. These authors showed that (a) men and women from all societies are capable of differentiating sexual dimorphism with no difficulty, even from a very early age; (b) a high percentage of men feel sexual attraction to women, just as women are attracted to men; (c) some percentage of men and women display dual attraction (towards both sexes); (d) some percentage are attracted to people of the same sex; and (e) a minimal percentage of men and women display no apparent sexual attraction towards either of the sexes (Busseri, Willoughby, Chalmers, & Bogaert, 2008;D'Augelli & Patterson, 2001;Diamond, 1993;Fernández, Quiroga, & Del Olmo, 2006a, 2006bLippa, 2007;Omoto & Kurtzman, 2006). Considering the large percentage of men attracted to women and of women attracted to men, in our time and our societies, these authors infer that sexual attraction can be operationalized by means of two clusters of items, defined either as a function of the object of attraction (attraction to women and to men), or as the specificity of their content (thoughts-cognitive aspect-, feelings-emotional aspect-, behaviors-observable FERNÁNDEZ, QUIROGA, DEL OLMO, BUIZZA, AND IMBASCIATI aspect,-and social image-hetero-appraisal aspect).…”
mentioning
confidence: 99%
“…In view of these results, we may conclude that, in the different countries analyzed to date (Spain, Italy & Peru), the assumptions underlying the elaboration of SAQ are ratified. This means that sexual attraction is shown in behaviors, thoughts, feelings and social image, organized around the two considered objects of attraction: women and men (Fernández et al, 2006;Fernández et al, 2006b;Fernández et al, 2009). Given that SAQ maintains its psychometric properties across the different countries evaluated to date, researchers may now substitute the single question on sexual attraction by an instrument that enables taking different facets of sexual attraction into account: thoughts, feelings, actions and social image (Busseri et al, 2008;Galliher et al, 2004;Giovazolias & Davis, 2001;Lippa, 2006;Rostosky et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory factor analyzes carried out with different versions of the SAQ support the hypothesis of two inversely related factors. However, in some cases, only a single bipolar factor has appeared (Fernández et al, 2006;Fernández, Quiroga, & Del Olmo, 2006b;Fernández et al, 2009).…”
Section: Instrumentmentioning
confidence: 99%